Art as a Language: Exploring the Challenges and Opportunities for English Language Learner Support in Elementary Art Classrooms - Butler, Alicia (East Carolina University)
Art education provides a powerful and unique platform for supporting English Language Learner (ELL) students in developing language skills through creative and engaging instruction. The visual, experiential, and collaborative nature of art offers significant opportunities to facilitate vocabulary acquisition and comprehension. However, elementary art teachers often face substantial challenges in maximizing this potential due to gaps in professional development (PD) and systemic barriers that hinder their ability to meet ELL students’ needs effectively. This study investigates these challenges by examining the PD opportunities available to elementary art teachers, the systemic obstacles they encounter, and the resources they require to better support ELL students in their classrooms. Using a mixed-methods approach, data were collected through surveys and interviews with elementary art teachers across North Carolina, providing a comprehensive analysis of their experiences, perceptions, and strategies. Results reveal a critical lack of targeted PD that equips art educators with the tools to implement language acquisition strategies. Additional systemic barriers, such as limited access to resources, insufficient collaboration time with ESL specialists, and inadequate institutional support, further compound these challenges. Despite these obstacles, findings underscore the immense potential of art instruction to enhance language learning through its inherently visual and interactive processes.
Keywords: Education, Art; Education, English as a Second Language